Intelligent Quotient of Schoolchildren at an Urban Community Kelurahan Utan Kayu, Jakarta - Titi Sularyo; Sudiyanto Sudiyanto; Sri Rochani Sudjarwo; E. Toto Atmodiwiryo (Paediatrica Indonesiana, 1978)
The I.Q. measurements of a group of 103 schoolchildren of an urban community at Kelurahan Utan Kayu, Jakarta, have been evaluated. The expected result of 92.4 as the mean I.Q. value is considered due to the not so favorable environmental conditions provided to meet the basic needs of children for their growth and development. Therefore every effort must be made to improve the environment in all its aspects in order to improve the health of the children and to provide them with the right parental stimulation so that they will be able to take more advantages of the available eduoational opportunities.